2019
DOI: 10.1002/jac5.1120
|View full text |Cite
|
Sign up to set email alerts
|

To tweet or not to tweet? A primer on social media for pharmacists

Abstract: Social media has evolved considerably since its humble beginnings in the late 1990s. Today, three billion individuals worldwide use social media. While its traditional use has been to connect with family and friends, social media has also been integrated into many other areas of society, including health care. Today, many health care professionals, including pharmacists, use social media for developing their own personal brand, professional networking, professional development, scholarly activity, pharmacy edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…In addition to Mendeley, Twitter has become a frequently used platform to share articles online. 15 Although we did not find an association between Twitter promotion and citation counts, two large, randomized studies 16,17 of articles published in cardiology and thoracic surgery journals demonstrated that Twitter promotion was associated with a significant increase in citation counts. However, both studies did not control for authors who may have had a significant online presence and self-promoted their published articles.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition to Mendeley, Twitter has become a frequently used platform to share articles online. 15 Although we did not find an association between Twitter promotion and citation counts, two large, randomized studies 16,17 of articles published in cardiology and thoracic surgery journals demonstrated that Twitter promotion was associated with a significant increase in citation counts. However, both studies did not control for authors who may have had a significant online presence and self-promoted their published articles.…”
Section: Discussioncontrasting
confidence: 66%
“…In recent years, social media in health care as a means to connect, communicate, and collaborate has grown substantially. When used appropriately, social media serves as an invaluable tool for health care professionals to increase engagement with learners, discuss and challenge emerging research, pursue professional development, expand social networks, engage in digital scholarship, and foster research publicity 60‐62 . The importance of developing a social media presence for pharmacists has been emerging and readers are suggested to review a recent publication by Dixon and colleagues to gain a comprehensive understanding on strategies to create an effective and sustainable social media profile 60 .…”
Section: The Intersection Between Social Media Infographics and Edumentioning
confidence: 99%
“…When used appropriately, social media serves as an invaluable tool for health care professionals to increase engagement with learners, discuss and challenge emerging research, pursue professional development, expand social networks, engage in digital scholarship, and foster research publicity 60‐62 . The importance of developing a social media presence for pharmacists has been emerging and readers are suggested to review a recent publication by Dixon and colleagues to gain a comprehensive understanding on strategies to create an effective and sustainable social media profile 60 . With regard to content delivered on social media, there is a symbiotic relationship that exists between high‐quality content and social media; without high‐quality content, social media loses its educational benefits, and without social media, no one will benefit from its content 63 .…”
Section: The Intersection Between Social Media Infographics and Edumentioning
confidence: 99%
“…The Sentinel Watch, a blog by American Sentinel University that offers degrees in nursing and healthcare management, encourages hospital administrators to have a presence on social media [44]. In addition, some healthcare organizations, including the American College of Clinical Pharmacy and American Association of Colleges of Pharmacy, have published reports or conducted webinars to provide advice on the importance of and how to build a digital brand through social media [45][46][47]. Social media is a platform that could be utilized to market services of the healthcare system or to provide access for complaints or appraisals in a quick manner [48].…”
Section: Healthcare Administrator Perspectivementioning
confidence: 99%